«АЛТЫН ҚАЗЫҚ»ТЫҢ ТЫҢ СЫРЛАРЫ - Утамбетова, А.Ж. (FAN va JAMIYAT, 2024)
The article is devoted to the novel-essay by K.Allambergenov «Алтын қазық», in which the scientist’s information about the son of Nurtai batyr Dzhangeldi is widely discussed.